The Use of Metaphors in Describing the Algerian Hirak in Western and Arab Literature: Case Study of Farrand’s The Algerian Dream and Jadaliyya e-Zine - GUEHEF, Hamza; Keddar, Abdelhakim; Ghedeir Bachir, Mostafa (جامعة الوادي - University of Eloued, 2023)
This research explores the metaphors depicted in academic literature by Algerian and Western writers. The Algerian perspective was represented by the articles featured in the web journal Jadalyyia, while The Algerian Dream book represented the Western perspective. The study aims to explore the metaphors used in Western and Arabic literature representing the Algerian Hirak. To achieve this aim, the study employed a descriptive case study. The analysis revealed that Western literature uses metaphors and their modifications to elicit feelings, provide vivid images, and frame the story involving the Algerian Hirak. Their goal is to encapsulate the movement's ethos, its revolutionary power, and the desire for a society that is more democratic and just. However, in Algerian literature, writers use a variety of metaphors to convey the significance and substance of the Algerian Hirak to create friendship and highlight the movement's revolutionary potential, they make use of cultural symbols, historical allusions, and language quirks that speak to Arab readers. It is significant to note that the precise metaphors employed in Arabic literature might change across different authors' works and interpretations of the Algerian Hirak in the Arab setting.
Literature and Civilization
Keywords: Algeria, Hirak, Metaphors, Social Movements.